Six-year experience of a hospital-based child protection team in Turkey - Şahin, Figen; Çepik-Kuruoğlu, Aslı; Demirel, Birol; Akar, Taner; Duyan-Çamurdan, Aysu; İşeri, Elvan; Demiroğulları, Billur; Paslı, Figen; Beyazova, Ufuk; Oral, Resmiye (The Turkish Journal of Pediatrics, 2009)
The objective of this article was to review the case series' profile followed up by the Gazi University Multidisciplinary Team for Child Protection and to describe the challenges in our child protection system. The cases referred to this team between February 2001 and January 2007 were analyzed. In addition to the clinical management, challenges encountered during follow-up due to gaps in the child protection system were reviewed. A total of 139 patients were referred to the team during the study period. Mean age for physical abuse, sexual abuse, and neglect were 8.9 +/- 6.2, 10.8 +/- 4.2, and 5.1 +/- 5.5 years, respectively. Sexual abuse was significantly less common while neglect was significantly more common in the 0-5 years of age group. In addition to the gaps within each link of the child protection system (medical, legal and social services) in Turkey, interagency collaboration seems to be inadequate. Hospital-based multidisciplinary teams can start such a collaboration.